Kajian Etnobotani Tumbuhan Jerangau (Acorus Calamus L) di Suku Dayak Sampit - Noorannisa, Luthfia (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The development of the digital era in Indonesia cannot be denied. Along with the rapid progress of the digital era, the fulfillment of basic needs such as food, clothing and shelter is also increasing and limited. Efforts that can be made can be from recording, utilizing, planting in an agricultural business to preserving it which involves various fields of science, including Classification, Study of Ethnobotany Utilization and Biotechnology. Ethnobotany is a botanical science that studies the relationship between humans and plants. There are 6 studies in ethnobotany including botany, linguistics, ecology, pharmacology, economics, and anthropology. The Sampit Dayak community has various types of local plants that are used for daily life, both as food, herbal medicine, and even for traditional rituals, one of the plants that is still used today is jerangau (Acorus calamus L). This study used an interview method with the snowball sampling technique while plant samples were obtained from the environment around Baamang in Sampit, to then observe the morphology and ecology of the place where jerangau grows. In the botanical study, it was found that jerangau is a herbaceous plant that has fibrous roots, compound flowers, and single leaves. Linguistic studies state that jerangau comes from the word "jera" because it makes you afraid of bad things coming again. Pharmacological studies of jerangau can be a medicine for bad breath, fever, and colds. This plant has ecological benefits, namely it can protect against river and gutter abrasion. Jerangau is economically very low, it can only be used as animal feed. Anthropologically, people use jerangau as protection for pregnant women and mothers who have just given birth.